‘PARADISE REGAINED’: CAN SUSTAINABLE DEVELOPMENT BE ACHIEVED WHEN THE PROTECTION OF FOREIGN DIRECT INVESTMENT IS AT STAKE? EXAMINING THE CASE STUDY OF VATTENFALL V GERMANY I - Carvalho, Viviane Cruz Alves de (Revista Eletrônica de Direito Processual, 2019)
Reconciliation between development and environmental protection is one of the greatest pressing issues of our times and should happen under a full integration model. In reality, however, political and ‘diplomatic tricks’ left the concept of SD open to interpretation not to bind policy decisions. Some have argued that SD is already inherent to the policy of most developed States. This study will demonstrate, however, that even in developed economies, the implementation of SD still faces difficulties because of the vagueness of the concept, which enables policy choices that prioritise the protection of FDI at the expense of environmental protection. The issues generated by these conceptual flaws are often aggravated by the actual filing or even by the threat of private expensive arbitration procedures, which generate a “chilling effect” on environmental regulation. The case of Vattenfall v Germany I will demonstrate that even a State with a strong governance system faced a foreign intrusion in its environmental policy choices as a result of being sued for EUR 1.4 billion in ICSID. The study concludes by suggesting that the achievement of SD can coexist with FDI as long as host States do not waive their policy space to regulate.